Efektivitas Kelompok Kerja Guru Dalam Meningkatkan Mutu Pembelajaran PAI SD Di Kecamatan Wanareja Kabupaten Cilacap - Sarno Hanipudin; Lastri Khasanah; Muhamad Habib; Ahmad Syaehu Umam Muttaqin (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2024)
This study aims to determine: (1) What are the activities of the Islamic Religious Education (PAI) Teacher Working Group (KKG) in Wanareja Sub-District in improving the quality of PAI learning in elementary schools. (2) The process of PAI learning in Wanareja Sub-District. (3) Is the Islamic Religious Education (PAI) Teacher Working Group (KKG) activities in Wanareja Sub-District effective in improving the quality of PAI learning in elementary schools.This study is a field research with a quantitative approach. The total population in this study consisted of 42 elementary school PAI teachers who participated in the KKG. There are two variables in this study: the independent variable (x) and the dependent variable (y). In the data collection process, the researcher used observation, interviews, documentation, and questionnaires.